2012
DOI: 10.1016/j.psychres.2011.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect forms of non-suicidal self-injury: Evidence for a distinction

Abstract: Non-suicidal self-injury (NSSI) involves deliberate acts (such as cutting) that directly damage the body but occur without suicidal intent. However, other non-suicidal behaviors that involve people mistreating or abusing themselves but that do not deliberately and directly damage bodily tissue may have much in common with NSSI. Such 'indirect' methods of self-injury might include involvement in abusive relationships, substance abuse, risky or reckless behavior, or eating disordered behavior. Using a community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 84 publications
6
116
1
1
Order By: Relevance
“…The results of the present review indicate that individuals who engage in NSSI self-reported greater impulsivity concurrently, relative to individuals who do not engage in NSSI (Arens et al, 2012;Claes & Muehlenkamp, 2013;Crowell et al, 2012;Di Pierro et al, 2012;Dir et al, 2013;Glenn & Klonsky, 2010;Lynam et al, 2011;Mullins-Sweatt et al, 2013;Ogle & Clements, 2008;St Germain & Hooley, 2012;Taylor et al, 2012). These differences were most pronounced for measures of negative urgency, and to a lesser extent for lack of premeditation and perseverance.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The results of the present review indicate that individuals who engage in NSSI self-reported greater impulsivity concurrently, relative to individuals who do not engage in NSSI (Arens et al, 2012;Claes & Muehlenkamp, 2013;Crowell et al, 2012;Di Pierro et al, 2012;Dir et al, 2013;Glenn & Klonsky, 2010;Lynam et al, 2011;Mullins-Sweatt et al, 2013;Ogle & Clements, 2008;St Germain & Hooley, 2012;Taylor et al, 2012). These differences were most pronounced for measures of negative urgency, and to a lesser extent for lack of premeditation and perseverance.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, individuals who engaged in NSSI from inpatient adolescent and adult samples reported greater impulsivity than individuals who did not engage in NSSI (i.e., motor impulsivity and non-planning as assessed on the BIS; Evren et al, 2012;Herpertz et al, 1997;McCloskey, Look, Chen, Pajoumand, & Berman, 2012). The association between impulsivity and NSSI was found with male (Evren et al, 2012) and female participants Crowell et al, 2012;Ogle & Clements, 2008), as well as among individuals with varying ethnic backgrounds, including Spanish , Italian (Di Pierro, Sarno, Perego, Gallucci, & Madeddu, 2012), American (Crowell et al, 2012;Dir et al, 2013;Ogle & Clements, 2008;St Germain & Hooley, 2012), Canadian (Cloutier et al, 2010), and German (Herpertz et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Second important factor effecting the development of SIB was the depression scores. Similarly, high depression scores have been also demonstrated among adolescents with SIB in the literature 3940. Other factors do not have statistically significant impact.…”
Section: Discussionmentioning
confidence: 68%
“…The terms selfinjury or non-suicidal self-injury that have gained ground in North America refer to behaviors performed without suicidal intent. Yet another distinction is made between direct and indirect self-injurious behavior (Nock, 2010;St Germain & Hooley, 2012). Indirect self-injurious behaviors might, for example, include involvement in abusive relationships, substance abuse and other risky or reckless behavior.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…Indirect self-injurious behaviors might, for example, include involvement in abusive relationships, substance abuse and other risky or reckless behavior. There can be an overlap between these behaviors, but there is empirical support for separating and distinguishing between direct and indirect forms of selfinjury (St Germain & Hooley, 2012).…”
Section: Definition and Classificationmentioning
confidence: 99%